AKSELERASI PEMBANGUNAN PERTANIAN WILAYAH TERTINGGAL MELALUI PENGUATAN KAPASITAS PETANI DAN KELOMPOK TANI - Kurnia Suci Indraningsih; Dewa K S Swastika (Forum penelitian Agro Ekonomi, 2021)
The livelihood of the people who live in underdeveloped regions mostly depends on the natural resources-based economy. Agriculture is still the main source of income for those living in disadvantaged regions. Most farmers have low agricultural knowledge and skills. To improve the economy in those areas, facilitating policies and funding are needed. Strengthening the capacity of farmers is also one of the important policies. The study aims to analyze the capacity building of farmers and farmer groups. The method used in the study is a review of various references. Although government support in funding and facilitation is needed, government support should not create dependence on farmers, instead, it should make farmers independent. Soft loans with simple procedures are believed to be more educated than providing free inputs assistance. The government should also prioritize counseling and mentoring to improve the capacity of farmers. Training of trainers for extension workers should be carried out regularly to update knowledge and improve competence, so they can transfer the latest knowledge and skills to farmers. Good knowledge and skills and high capacity can create strong and independent farmers, in turn, they are able to become productive rural economic actors.